Fault Current Limiters Enhancing Power System Stability and Safety (Global Journals of Research in Engineering, 2025)
This paper presents the overview of Fault Current Limiters its evolution with timeline types and alternate options The study can help the user give more insight to various types and alternate options for selection of fault current limiter The paper reveals that FCL is crucial for limiting fault current and enhancing power system stability reliability and safety
Keywords: fault current limiters; resistive FCL; inductive FCL; superconducting FCL; solid state FCL; hybrid FCL; power system stability